Adaptation Of Dutch Colonial Architecture to Palembang's Humid Tropical Climate - Lestari, Endang Sri; Purnamasari, Evi (Proceedings of the international conference of contemporary affairs in architecture and urbanism-ICCAUA, 2022)
The Dutch Colonial Architecture in the Talang Semut Palembang area notes that there is a lot of diversity in the style and function of the building as well as the historical journey that includes the adaptation process. This adaptation process is observed in the design world today and in the future. Proof of the adaptation process is carried out by calculating physical analysis to find out the extent to which this tropical consideration is carried out. The process of adapting Dutch Colonial architecture to a humid tropical climate is expected to be able to provoke the creativity of architects in designing buildings properly without using artificial air conditioning equipment. The arrangement of interior layout, outer space and mass management as well as the environmental pattern of this Dutch residential area with the completion of the detailed construction planned to anticipate tropical problems have really been carried out properly.